2023
DOI: 10.1186/s12943-023-01766-2
|View full text |Cite|
|
Sign up to set email alerts
|

The function and mechanisms of action of circular RNAs in Urologic Cancer

Abstract: Kidney, bladder, and prostate cancer are the three major tumor types of the urologic system that seriously threaten human health. Circular RNAs (CircRNAs), special non-coding RNAs with a stabile structure and a unique back-splicing loop-forming ability, have received recent scientific attention. CircRNAs are widely distributed within the body, with important biologic functions such as sponges for microRNAs, as RNA binding proteins, and as templates for regulation of transcription and protein translation. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 203 publications
1
5
0
Order By: Relevance
“…This indicates an opposing effect between hsa_circ_0036474 and miR-223-3p in EC109 cells, and cir-cRNA-0036474 could have significant effects by modulating miR-223-3p expression. These obtained results were in agreement with the other studies [15,16], indicating that some key circRNAs could play a role through related miR-NAs. Notably, the hsa_circ_0036474 levels were markedly increased within the EC109 cells.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates an opposing effect between hsa_circ_0036474 and miR-223-3p in EC109 cells, and cir-cRNA-0036474 could have significant effects by modulating miR-223-3p expression. These obtained results were in agreement with the other studies [15,16], indicating that some key circRNAs could play a role through related miR-NAs. Notably, the hsa_circ_0036474 levels were markedly increased within the EC109 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have shown that noncoding RNAs govern carcinogenesis in bladder cancer (143)(144)(145)(146). Noncoding RNAs are transcribed from DNA, but not translated into proteins, including microRNAs (miRNAs), lncRNAs (log noncoding RNAs), siRNAs (small interfering RNAs), snRNAs (small nuclear RNAs) and piRNAs (147)(148)(149).…”
Section: Noncoding Rnas Target E3 Ligasesmentioning
confidence: 99%
“…Circular RNAs (circRNAs), which have covalently linked ends, have attracted increasing attention because of their potential for biological activity in different clinical fields, including cancer biology [ 4 , 5 ]. It was shown that circRNAs isolated from urine can serve as biomarkers for different urological diseases [ 6 ]. CircRNAs are generated during pre-mRNA splicing when a downstream 5′ splice site is joined to an upstream 3′ splice site [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%